A Prospective Randomized Trial Comparing Percutaneous Local Ablative Therapy and Partial Hepatectomy for Small Hepatocellular Carcinoma - Chen, Min-Shan (2006)
OBJECTIVE: To compare the results of percutaneous local ablative therapy (PLAT) with surgical resection in the treatment of solitary and small hepatocellular carcinoma (HCC). SUMMARY BACKGROUND DATA: PLAT is effective in small HCC. Whether it is as effective as surgical resection in the long-term survivals remains unknown. METHODS: We conducted a prospective randomized trial on 180 patients with a solitary HCC ≦5 cm to receive either PLAT or surgical resection. The patients were regularly followed up after treatment with physical examination, blood, and radiologic tests. RESULTS: Of the 90 patients who were randomized to PLAT, only 71 received PLAT because 19 withdrew their consent. Of the 90 patients who were randomized to surgical resection, a single Couinaud liver segment resection was carried out in 69 patients, 2 segments in 16 patients, and 3 or more segments in 3 patients. Ethanol injection was given during open surgery in 2 patients. Only 1 patient died after surgical resection within the same hospital admission. Posttreatment complications were more often and severe after surgery than PLAT. The 1-, 2-, 3-, and 4-year overall survival rates after PLAT and surgery were 95.8%, 82.1%, 71.4%, 67.9% and 93.3%, 82.3%, 73.4%, 64.0%, respectively. The corresponding disease-free survival rates were 85.9%, 69.3%, 64.1%, 46.4% and 86.6%, 76.8%, 69%, 51.6%, respectively. Statistically, there was no difference between these 2 treatments. CONCLUSION: PLAT was as effective as surgical resection in the treatment of solitary and small HCC. PLAT had the advantage over surgical resection in being less invasive.